Impact of the COVID-19 Pandemic on the Developmental Outcomes among Korean Kinship Foster Care Children: Gender Differences - Hyunah Kang; Ick-Joong Chung; Sehyeon Oh (Societies, 2023)
(1) Background: This study explored changes before and during the COVID-19 pandemic in terms of developmental outcomes among kinship foster care children in the Republic of Korea: and gender differences in the changes; (2) Methods: The study analyzed the data of 217 kinship care children who participated in both the first- and second-wave surveys of the Panel Study of Korean Foster Care Children. As the main statistical methods, we utilized repeated-measures ANOVA and analysis of covariance (ANCOVA); (3) Results: Analysis of developmental outcomes measured before and during the pandemic showed no significant changes. However, significant interaction effects existed between time (before and during the pandemic) and gender, indicating that boys and girls recorded different patterns of change before and during the COVID-19 pandemic; (4) Discussion:During the COVID-19 pandemic, girls experienced negative changes in most areas of development, whereas boys experienced positive changes. The policy and practical implications for foster care children in Korea were discussed.